2022
DOI: 10.5713/ab.21.0198
|View full text |Cite
|
Sign up to set email alerts
|

Effect of social order, perch, and dust-bath allocation on behavior in laying hens

Abstract: Objective: The objective of this study was to determine the effects of different social ranking order (SRO) and the enrichments (perch and dust-bath) allocation (EA) on behavior of laying hens in furnished cage.Methods: A total of 4 weeks in experiment period. 216 Hy-line brown layers beak-trimmed at 1 d of age were selected randomly at 14 weeks of age from a commercial farm, and randomly divided into 36 cages with 6 hens in each cage. High enrichments (perch and dust-bath) allocation (HEA) and low enrichments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…A similar result was observed by Baxter et al [ 156 ], who found that approximately 22,000 broilers receiving oat hulls as dustbathing substrate showed better gait score and encouraged dust-bathing and foraging, but must be a part of a complementary enrichment program where other biological needs of the animals are covered. Furnished cages in 216 Hy-line brown layers have also shown that perches and dust-bath enrichment must consider social ranking since this can affect behavioral expression [ 157 ]. As Sandilands et al [ 158 ] have shown, providing scratch mats to laying hens does not always have a beneficial effect on behavior or productive parameters, and the study regarding how to use the seeking system to provide welfare is still ongoing.…”
Section: Motivation and Satietymentioning
confidence: 99%
“…A similar result was observed by Baxter et al [ 156 ], who found that approximately 22,000 broilers receiving oat hulls as dustbathing substrate showed better gait score and encouraged dust-bathing and foraging, but must be a part of a complementary enrichment program where other biological needs of the animals are covered. Furnished cages in 216 Hy-line brown layers have also shown that perches and dust-bath enrichment must consider social ranking since this can affect behavioral expression [ 157 ]. As Sandilands et al [ 158 ] have shown, providing scratch mats to laying hens does not always have a beneficial effect on behavior or productive parameters, and the study regarding how to use the seeking system to provide welfare is still ongoing.…”
Section: Motivation and Satietymentioning
confidence: 99%
“…Chickens acquire social behaviour from each other by learning to identify visual and auditory stimuli (Wang et al, 2022). The flock structure is hierarchical with male dominance over hens, and the hierarchy determined by the pecking order.…”
Section: Introductionmentioning
confidence: 99%
“…is restricted (Quieroz and Cromberg, 2006;Wang et al, 2022). Dominance-subordination interactions, maintained by means of aggressive behaviour, contribute to maintaining stability in the group (Bhanja and Bhadauria, 2018;Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations